Cognitive «portrait» of children with mental retardation - T. S. Kaminskaya; L. G. Khachatryan; E. V. Kasanave; I. V. Kaminskiy (Лечащий Врач)
Within the framework of a cross-sectional analytical study, the structure of cognitive function disorders and psychoemotional status in children with delayed psychoverbal development was determined. 132 children aged 5-11 years were examined: 58% boys and 42% girls. Diagnostics was carried out using a computer psychophysiological complex «Psychomat-99». Methods for studying the sensorimotor reaction, dynamic and static coordination, correction test, Mnemotest and Luscher's test were used to assess the psycho-emotional state. Structural analysis of children with delayed psychoverbal development verified that the most pronounced insufficiency is noted in the speech function – in 98%, a deficit in auditory speech memory is detected in 73%, voluntary attention – in 63%, a lack of visual-spatial memory in 67%, visual-spatial perception – in 59%, thought disorders – in 50%. Less common are violations of executive functions (38%) and emotional sphere (14%). A detailed assessment, taking into account the etiopathogenetic factor of delay in psychoverbal development, revealed that patients with genetic pathology often have problems in the amount of voluntary attention, visuospatial memory, visuospatial perception and thinking. In children with organic lesions of the central nervous system, more often than in other groups, the ability to formulate a speech statement is preserved. Speech delay in these cases is characterized mainly by disturbances in sound pronunciation, in particular dysarthria and dyslalia. In patients with developmental delay with an established psychiatric diagnosis, there is a more pronounced cognitive deficit in comparison with other groups in all areas of intelligence. The use of computer test systems helps to objectively assess the intellectual level of children with mental retardation. The form of testing makes it possible to more effectively keep patients' attention on completing tasks than when using paper media in the process of neuropsychological examination on the computer psychophysiological complex «Psychomat-99». The advantages of computer test systems also lie in the uniformity of the provision of material and the minimization of the subjective component in the interpretation of the results of the study. Domestic, highly informative device for testing «Psychomat-99» can be recommended for use in practical children's health care.